The Effectiveness of Fried Catfish Cake In Increasing Hemoglobin Levels And Oxygen Saturation In Blood In Pregnant Women - Iis Sopiah Suryani; Maria Ulah Jamil; Novianti Rizki Amalia; Ajeng Maharani Pratiwi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Iron deficiency anemia mainly affects pregnant women, lactating women and women of childbearing age in general. Many things change in pregnant women in the third trimester of pregnancy. In the third trimester, blood volume is still increasing so pregnant women need foods rich in iron and vitamin C for good iron absorption. Catfish is one of the foodstuffs that is easy to serve and the price is cheaper than other fish. The nutritional content of catfish will increase with the right way of processing. Fresh catfish contains 1.0 mg of iron. After frying, it becomes 1.2 mg. With the condition of pregnant women who are prone to anemia, pregnant women must fulfill their nutrition by adding additional food, which can be in the form of snacks made from catfish so that their fe needs will be met. Catfish, apart from being processed into meatballs, can also be processed into the fried catfish cake. Quasi-experimental research type non randomized pre test post test. The research subjects were pregnant women in the third trimester. The analysis of this study used the Paired t test. Results: the results of research that has been conducted regarding differences in Hb levels in pregnant women in the third trimester before and after being given fried catfish cake, it was found that there were differences in Hb levels before and after treatment, this result was evidenced by the results of the t statistical test where the tcount was 10,816 with a significance level of ρvalue of 0.000, there is a significant difference because ρvalue is smaller than α (0.05). Meanwhile, for oxygen saturation with the Wilcoxon test statistic, the Z value is -3.345 with a significance level of ρvalue of 0.001, Thus before and after treatment there is a significant difference because the value is smaller than α (0.05). The brain of fried catfish cake is effective in increasing hemoglobin levels and oxygen saturation in the blood in third trimester pregnant women.